Biodiversity’s Impact on Greenhouse Gas Emission Reduction at PT Pabrik Kertas Tjiwi Kimia Tbk: Pengaruh Keanekaragaman Hayati terhadap Penurunan Emisi Gas Rumah Kaca di PT Pabrik Kertas Tjiwi Kimia Tbk - Niken Kartika Nahdya Rokhimanillah; R. Mohammad Alghaf Dienullah; Sekarsari Wibowo; Abdillah Akmal Karami (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
Increasing greenhouse gas (GHG) emissions from industrial activities have become a serious environmental concern, making carbon sequestration through vegetation an important mitigation strategy, particularly in industrial areas where green open spaces serve as natural carbon sinks. This applied study analyzed the influence of biodiversity on GHG emission reduction through vegetation carbon stock estimation across four strata, namely trees, poles, saplings, and undergrowth, in the Mill area (estimated 10 Ha) and Conservation area (3.52 Ha), using an allometric approach from literature converted into tCO₂e, with statistical analysis conducted using the Spearman correlation test and Kruskal-Wallis test due to non-normal data distribution and small sample size. The highest carbon sequestration was recorded in the tree strata at 147.996 tCO₂e (90.7% of total), while the lowest was recorded in the undergrowth strata at 2.190 tCO₂e in the Mill area, with total sequestration of 163.032 tCO₂e in the Mill area and 20,233 tCO₂e in the Conservation area. The results of this applied study concluded that vegetation effectiveness in reducing GHG emissions is more determined by biomass accumulation rather than species diversity, as evidenced by the dominance of a single species (trembesi) contributing significantly to carbon stocks. Greening strategies should prioritize planting high-biomass vegetation such as trembesi (Samanea saman), mahogany (Swietenia mahagoni), and acacia (Acacia mangium), and be integrated with other emission reduction efforts such as energy efficiency and carbon capture technology.